Implementation of deep learning-based instruction integrating pertuturen sulang silima local wisdom to enhance elementary students' social attitudes and mathematical creativity - Putu Kerti Nitiasih; Agus Junsion Naibaho; Putu Nanci Riastini; Ni Nyoman Trisna Herawati (Indonesian Journal Education, 2026)
This study aims to systematically analyze the implementation of the deep learning approach in elementary mathematics education, particularly its integration with local wisdom and its impact on students' mathematical creative thinking skills and social attitudes. The study employed a Systematic Literature Review (SLR) method to analyze 15 scientific articles published between 2017 and 2025 that were relevant to the research topic. The article selection process followed the PRISMA framework, which consists of the identification, screening, eligibility, and inclusion stages. The findings indicate that integrating deep learning with ethnomathematics and local wisdom significantly enhances students' conceptual understanding, mathematical creativity, and social character development. Furthermore, the incorporation of local cultural contexts, such as traditional games and community traditions, has been shown to increase students' engagement in learning activities. This study recommends the development of contextual and transformative deep learning-based instructional models that integrate local wisdom into elementary school curricula to support meaningful and sustainable mathematics learning.